Performance Evaluation Of Wavelet-Based Algorithm For Printed Circuit Board (PCB) Inspection - Ibrahim, Zuwairie (Penerbit UTM Press, 2001)
Image difference operation is frequently used in automated printed circuit board (PCB) inspection system as well as in many other image processing applications. The inspection system performance depends critically on the speed of this operation, which is a common problem related to the image difference. The goal of our technique is to achieve real time inspection using wavelet transform. This paper presents a new wavelet-based algorithm for image difference, which computes image difference to the output of the wavelet transform. The results of applying the technique to PCB images showed significant improvement on the traditional image differencing.